Symposium 12: A Blended Learning Approach for Teaching Professionalized Action - Schrittesser, Ilse (Proceedings of the International Conference on Networked Learning, 2004)
In this paper, we present a blended learning design which we use in an academic course programme that deals with the professionalization of teachers. The focus of the paper will be the evaluation of two courses of this programme by our students. The courses are both conceptualized as hybrid learning structures relying on face[1]to-face meetings as well as distance learning sequences. We worked with two different platforms, one that is technically quite basic, mainly offering an organizing and an up- and download function, as well as a forum; and one that is rather complex providing interactive patterns in combination with knowledge and content management tools. Our interest lies in two predominant questions: first we want to find out which specific resources platforms can offer for our teaching objective - educating for excellence in professionalized pedagogical job fields. In this connection, we also look for if and to which extent face-to-face meetings are crucial to the learning process. The second question we pose, is if and in which way our students consider the learning platforms we worked with as a means of facilitating their learning processes. We will first discuss our concepts of learning and of professionalized action; consequently, we will describe our course design; finally, we will present, compare and interpret the results of two non-standardized questionnaires that the students had to answer in order to give us feedback on their experiences with the platform work in both courses and with both platforms.